2014
DOI: 10.9758/cpn.2014.12.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Potential Molecular and Cellular Mechanism of Psychotropic Drugs

Abstract: Psychiatric disorders are among the most debilitating of all medical illnesses. Whilst there are drugs that can be used to treat these disorders, they give sub-optimal recovery in many people and a significant number of individuals do not respond to any treatments and remain treatment resistant. Surprisingly, the mechanism by which psychotropic drugs cause their therapeutic benefits remain unknown but likely involves the underlying molecular pathways affected by the drugs. Hence, in this review, we have focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…29 ) As a result of this receptor binding there were secondary changes in the intracellular signal transduction pathways and activity of nerve growth factors, effects that were similar to classical mood stabilizers like lithium. 30 )…”
Section: Main Subjectsmentioning
confidence: 99%
“…29 ) As a result of this receptor binding there were secondary changes in the intracellular signal transduction pathways and activity of nerve growth factors, effects that were similar to classical mood stabilizers like lithium. 30 )…”
Section: Main Subjectsmentioning
confidence: 99%
“…Psychiatric medications have shown inconsistent responses to the cAMP cascade. Previous study demonstrated that haloperidol increased cAMP levels, chronic usage of clozapine has been found to decrease cAMP levels [ 59 ]. The forward MR analysis identified PDE1A as a risk factors for ASD, while suggesting potential protective effects of PDE2A in SCZ and TS.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that during 3- and 6-month follow-up, clinical attention deficit symptoms were negatively correlated with the relative expression of miR-4655-3p and miR-7641 [ 23 ]. Some available data have suggested that therapy with psychotropic drugs (specifically, antipsychotics, antidepressants, and mood stabilizers) appears to have complex and region-dependent effects on epigenetic mechanisms [ 24 ]. MPH has been shown to upregulate the expression of Homer 1a and to ameliorate ADHD-like behaviors [ 25 ].…”
Section: Introductionmentioning
confidence: 99%